Social Skills Via Emotional intelligence: Language Learning - Yıldırım, Osman (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
The aim of this essay to draw an outline of the effect of various types of intelligence, paying particular attention to the concept of so called "Emotional Intelligence" with a language teacher's perspective. Throughout the essay it is aimed to create an awareness of different intelligence capacity of each individual learner in an ideal language teaching environment. While doing this literature on the area has been scanned and case studies have been performed on learners of various cultural and geographical backgrounds. In literature, many quantitative findings indicate that there is a significant relationship between academic achievement and emotional intelligence skills. The importance of understanding Emotional intelligence (El) skills and social intelligence (SI) has gravitated form the business management to training activities. This study aimed at exploring the impact of social intelligence and emotional intelligence on the language learning. To this end, a research has been conducted on the students of vocational school (n=280) of two private vocational schools in Istanbul. In the research, participants emotional intelligence was assessed by the Emotional Competence Inventory (ECI, 2nd Version) developed by Boyatzis and Goleman and the Resilience Scale for Adults (RSA-scale) proposed by Hjemdal, Friborg, Martinussen, and Rosenvinge. According to the results, a strong relationship was revealed among emotional intelligence, social intelligence and language learning.
Keywords: Social Intelligence; Emotional Intelligence; Language Learning; Sosyal Zeka; Duygusal Zeka; Dil Öğrenmek